Pengaruh sistem pengukuran kinerja strategis terhadap kinerja manajerial, kejelasan peran dan konflik peran sebagai mediasi (survei pada bank di pekanbaru) - Selfira Ivani; Vince Ratnawati; Nurazlina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of strategic performance measurement systems on managerial performance with clarity of roles and conflict mediation role as a banking enterprise in the city of Pekanbaru.Population in this research is all the banks in the city of Pekanbaru to sample the lower and middle level managers. Methods of data collection using questionnaires. Analysis of the data in this study using the Partial Least Square (PLS).Results of hypothesis testing in this study suggests that strategic performance measurement system has a positive effect on role conflict, strategic performance measurement system has a significant positive effect on role clarity, role conflict had no significant effect on the performance of manjerial, role clarity has no significant effect on managerial performance, strategic performance measurement system has a significant positive effect on managerial performance, and clarity of roles and role conflict did not mediate the relationship between strategic performance measurement systems on managerial performance.Keywords: managerial performance, strategic performance measurement systems, role clarity, role conflict.